Design of path generating compliant mechanisms by evolutionary optimization of topology and shape - Shamim Akhtar. (2008)
This work looks into the design and synthesis of such path generating compliant mechanisms by topology and shape design optimization. The optimization is done using a specially formulated evolutionary algorithm together with an efficient geometry representation scheme called the Morphological Representation Scheme.